PENGARUH KEBANGSAAN ANGGOTA DEWAN PADA KINERJA PASAR (Studi Empiris pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia) - Ketut Arya Bayu Wicaksana; I Putu Astawa (Jurnal Analisis Manajemen, 2011)
In corporate governance literatures, board diversity is often assumed to increase board efficacy and monitoring, thus increase market performance. In this study board is defined as the combination of board of commissioners and directors since Indonesia uses two-tier board system. The purpose of this research is to investigate the effect of board diversity as measured by board members nationality on firms market performance as measured by price to book value ratio. This research also used company size and industry type as control variables. Samples consisted of 52 companies in 2006, 69 companies in 2007, and 45 companies in 2008, totalling 166 observation. All sample companies were listed at Indonesia Stock Exchange from the year 2006 until 2008. The hypothesis test using multiple regression analysis showed that board members nationality does not have any significant impact on firms market performance. On the other hand, size and industry type do have significant effects on firms market performance.